Raising a Laugh: Gift for Community Building or Disease to Be Remedied - Lumsden, Basil (The American Benedictine review, 2024)
This article examines the relationship between anger and laughter in the context of Benedictine community life. It explores the cultural understandings of laughter and joking in ancient Rome and their influence on Saint Benedict's monastic Rule. The article discusses the use of scurrility in Roman society and its impact on comedy, highlighting the potential harm of jokes that exploit human suffering. It suggests that St. Benedict encourages intelligent and community-building laughter in the monastery, while discouraging offensive or inappropriate humor. The text also provides historical context on the ancient Roman world and the struggles faced by its non-elite population, emphasizing the role of humor as a means of escape and catharsis.